A novel ion-imprinted polymer based on the principle of ion exchange by bulk polymerization for specific recognition and adsorption of nitrate in polluted groundwater. (February 2023) - Li, Wende; Li, Yan; Cai, Peiyao; Zhang, Mengyue; Xia, Tian; Liang, Xue; Xiao, Wei; Dong, Jun
Abstract: A novel NO3 − ion imprinted polymer (IIP-NO3 − ) was successfully synthesized based on the principle of "ion exchange" and the method of "bulk polymerization". The NO3 − anions, cationic monomers dimethyldiallylammonium chloride (DMDAAC) and acrylamide (AM) was used as template ions and functional monomers respectively. The material characterization showed that IIP-NO3 − has an irregular porous structure. The maximum nitrate adsorption capacity of IIP-NO3 − on NO3 − was 48.486 mg/g under an optimal preparation condition. The isothermal adsorption (R 2  = 0.9947) of IIP-NO3 − for NO3 − basically conformed to the Langmuir model. The adsorption process followed with the pseudo-secondary order kinetic model (R 2  > 0.99), and it can reach equilibrium within 5 min. The IIP-NO3 − had an obviously lower adsorption capacity for another common anion NO2 −, HCO3 −, SO4 2− ions in groundwater pollution than NO3 − ions. The recognition selectivity coefficient of IIP-NO3 − for NO3 − ions were 2.839, 6.450, 1.773 respectively due to the imprinted effect. And this ion imprinted polymers with high selectivity to nitrate can be combined with the chemical reduction and the electrochemical reduction method, so as to improve the nitrate chemical reduction efficiency and reduce the regeneration cost of the IIP-NO3 − .